The Influence of Psychological Capital and Affective Commitment on Organizational Citizenship Behavior of Hospital Staff - Puspitaloka Mahadewi, Erlina; Muchtadin, Muchtadin (International Journal of Science, Technology & Management, 2024)
Organizational Citizenship Behavior (OCB) is important to apply to hospital staff. This research aims to determine the simultaneous and partial influence of psychological capital and affective commitment on OCB. Respondents were 196 officers from two hospitals in Indonesia. The sampling method uses stratified random sampling. The data analysis method uses multiple linear regression. Data was processed with the help of Jamovi 2.3.28 software. The research results found that psychological capital and affective commitment had a significant positive effect on OCB both partially and simultaneously. Hospital management can increase the voluntary behavior of its staff in working beyond formal rules by increasing psychological capital such as self-efficacy, hope, optimism, resilience. Factors that increase affective commitment also need to be implemented so that officers' OCB increases, followed by better service provided. Future researchers can limit the study population to certain areas and combine private and government hospitals to obtain greater generalization. Future researchers can add other variables such as work motivation and job satisfaction to the simultaneous and partial effects.